An innovation Systems Approach to Sustainability Transitions Between Qatar and Jordan by Using SAP Software System - Khaloud AL-SULAITI; Houda ALEQEDAT (Sekolah Tinggi Manajemen IPMI, 2019)
This paper aimed to discuss how and where SAP software system can be used. It addresses relevant areas including linear innovation model, multi-level perspective, innovation systems and factors of innovation, factors of innovation, innovation management, circular economy, sustainability transitions, and SAP software system in terms of history, use, digital circular economy business model toolkit, and the difference between linear SAP and circular SAP solutions. It also compares the use of SAP in Qatar and Jordan.